Student Experience in Developing Clinical Abilities through Nursing Education - Edison Kabak (GLOBAL HEALTH SCIENCE GROUP, 2026)
Clinical capability development is a crucial component of nursing education, enabling the production of competent and ethical nurses. Clinical education emphasizes not only technical skills but also the formation of professionalism, soft skills, and moral values. This study aims to understand the experience of nursing students in developing clinical abilities through the clinical education process. The study employed a qualitative phenomenological approach with 12 final-semester nursing students who were purposively selected. Data was collected through in-depth interviews and was analyzed thematically. The analysis involves identifying units of meaning, structuring themes and subthemes, and verifying these interpretations with participants to ensure their accuracy. The findings show four main themes: (1) clinical readiness and application of theory, students experience initial challenges in applying theory to real practice; (2) mentoring and support, which improves technical skills and confidence; (3) self-reflection and self-learning, which strengthens the understanding of self-improvement practices and strategies; (4) development of soft skills and professionalism, including effective communication, teamwork, and the application of professional ethics. The interaction between practical experience, guidance, reflection, and professional development forms a holistic and continuous clinical learning process. Clinical education provides a well-rounded experience to shape students' technical abilities, soft skills, and professionalism so that they are prepared to become competent and responsible nurses.